Imaging features of triple-negative breast cancers according to androgen receptor status. Issue 114 (May 2019) - Candelaria, Rosalind P.; Adrada, Beatriz E.; Wei, Wei; Thompson, Alastair M.; Santiago, Lumarie; Lane, Deanna L.; Huang, Monica L.; Arribas, Elsa M.; Rauch, Gaiane M.; Symmans, W. Fraser; Gilcrease, Michael Z.; Huo, Lei; et al.
Graphical abstract: Highlights: TNBC is a heterogeneous collection of breast cancers that is defined by the lack of ER, PR and HER-2 expression. The luminal androgen receptor (LAR) subtype of TNBC is associated with lower rates of pathologic complete response. Androgen receptor (AR) status is a surrogate immunohistochemical marker for the LAR subtype of TNBC. Imaging surrogates of the chemoresistant LAR subtype could also be potentially identified. AR+ TNBC significantly associates with masses with high density, calcifications, and irregular shape. Abstract: Objective: Different molecular subtypes of triple-negative breast cancer (TNBC) have previously been identified through analysis of gene expression profiles. The luminal androgen receptor (LAR) subtype has been shown to have a lower rate of pathologic complete response to neoadjuvant chemotherapy than other TNBC subtypes. The purpose of this study was to determine if the imaging features of TNBCs differ by AR (androgen receptor) status, which is a surrogate immunohistochemical (IHC) marker for the chemoresistant LAR subtype of TNBC. Materials and methods: This sub-study was part of a clinical trial in patients with stage I-III TNBC who were prospectively monitored for response while receiving neoadjuvant systemic therapy (NAST) at a single comprehensive cancer center. This interim imaging analysis included 144 patients with known AR status measured by IHC. AR-positive (AR+) tumors were defined as those in which at least 10% of tumor cells had positive nuclear AR staining. Two experienced, fellowship-trained breast radiologists who were blinded to the IHC results retrospectively reviewed and reached consensus on all imaging studies for the index lesion (i.e., mammogram, ultrasound, and breast magnetic resonance imaging). The index lesion for each patient was reviewed and described according to the fifth edition of the Breast Imaging Reporting and Data System lexicon. Logistic regression modeling was used to identify imaging features predictive of AR status. p  ≤ 0.05 was considered statistically significant. Results: Univariate logistic regression models for AR status showed that AR+ TNBC was significantly associated with heterogeneously dense breast composition on mammography ( p  = 0.02), mass with calcifications ( p  = 0.05), irregular mass shape on mammography ( p  = 0.03), and irregular mass shape on sonography ( p  = 0.003). Multivariate logistic regression models for AR status showed that AR+ TNBC was significantly associated with heterogeneously dense breast composition on mammography ( p  = 0.01), high mass density on mammography ( p  = 0.003), and irregular mass shape on sonography ( p  = 0.0004). Conclusion: The imaging features of TNBCs differ by AR status. Multimodality breast imaging may help identify the LAR subtype of TNBC, which has been shown to be a subtype that is relatively resistant to neoadjuvant chemotherapy.